2001
DOI: 10.1096/fj.00-0474fje
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Smad signaling by protein kinase C

Abstract: Cross talk between transforming growth factor b(TGF-b) serine/threonine kinase receptor signaling and tyrosine kinase receptor signaling modulates cell responsiveness to polypeptide growth factors regulating cell proliferation, differentiation, and apoptosis. Here we provide a mechanism through which Smad-dependent TGF-b signaling is modulated by protein kinase C (PKC). PKC, for example, is activated downstream of tyrosine kinase receptors. We show that PKC directly phosphorylates receptor-regulated Smad prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
1
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 32 publications
(48 reference statements)
5
133
1
10
Order By: Relevance
“…However, as SB431542 partially blocked these responses, the phosphorylation of Smad-1/-5 appears to be in part secondary to the activation of ALK5. TGF-b1 can also act through receptor-dependent, but Smadindependent pathways, including the activation of mitogen-activated protein kinase (Blanchette et al, 2001), c-Jun N-terminal kinase (Engel et al, 1999) and protein kinase C (Yakymovych et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, as SB431542 partially blocked these responses, the phosphorylation of Smad-1/-5 appears to be in part secondary to the activation of ALK5. TGF-b1 can also act through receptor-dependent, but Smadindependent pathways, including the activation of mitogen-activated protein kinase (Blanchette et al, 2001), c-Jun N-terminal kinase (Engel et al, 1999) and protein kinase C (Yakymovych et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…MEKK1 or JNK enhanced Smad phosphorylation, nuclear localization, and Smad-mediated transcription (44,45). In contrast, the phosphorylation of R-Smads at the linker domain or MH-1 domain induced by Ras/Erk/MAPK, CDK2/4, and PKC inhibited the activation of Smad signaling (23,43,46,47). Yakymovych et al (23) reported that PKC activation resulted in the phosphorylation of the MH1 domains of Smad2 and Smad3 to abrogate DNA binding of Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have reported that PKC interacts with the TGF-h/BMP signaling pathway (23)(24)(25). PKC-dependent phosphorylation of the MH1 domain of TGF-h-specific Smads (Smad2/3) led to down-regulation of the growth-inhibitory and apoptotic action of TGF-h (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional kinases, e.g. MEKK-1, CaMKII, protein kinase C, and CKε, target R-Smads and regulate Smad-dependent transcriptional responses [36][37][38][39], and TGF-β may also induce Smad phosphorylation in the linker region as well as at the SXS motif [31,32]. Thus, the Smad linker region is emerging as an important and critical regulatory platform in the fine-tuning of TGF-β signaling.…”
Section: Phosphorylation and Dephosphorylation Of R-smads In The Linkermentioning
confidence: 99%